2010
DOI: 10.2174/092986710791331031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Features of the Mitochondrial Enzyme Ornithine Transcarbamylase: A Possible New Role as a Signaling Factor

Abstract: Ornithine transcarbamylase (OTC; EC 2.1.3.3) is a one-carbon-unit transferring enzyme that synthesizes citrulline using ornithine and carbamoylphosphate as substrates. It is involved in the metabolic transformation of arginine and proline, and it participates in the urea cycle in vertebrates and in the formation of putrescine in plants. Its enzymatic reaction is consistent with a ping-pong mechanism. OTC is expressed in a large variety of organisms from bacteria to mammals. Its gene can be regulated by glucoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…4). OTC, a one‐carbon‐unit transferring enzyme that synthesizes citrulline using ornithine and carbamoylphosphate as substrates, is expressed in a large variety of organisms, from bacteria to mammals 59. Inborn errors associated with a deficiency of OTC activity cause mainly urea cycle‐related disorders, and lead to hyperammonemic states, which may become lethal.…”
Section: Discussionmentioning
confidence: 99%
“…4). OTC, a one‐carbon‐unit transferring enzyme that synthesizes citrulline using ornithine and carbamoylphosphate as substrates, is expressed in a large variety of organisms, from bacteria to mammals 59. Inborn errors associated with a deficiency of OTC activity cause mainly urea cycle‐related disorders, and lead to hyperammonemic states, which may become lethal.…”
Section: Discussionmentioning
confidence: 99%
“…It is formed by two distinct structural domains that surround a deep cleft, linked by two long interdomain helices (h5 and h12; Figure 2B). Both structural domains have an αβα-topology, basically consisting of a central 5-stranded parallel β-sheet with α-helices on both sides (Shi et al, 2000;Diaz-Munoz and Hernandez-Munoz, 2010). Each subunit contains one active site situated at the hinge between its two domains.…”
Section: Protein Maturation Targeting and Secondary Modificationmentioning
confidence: 99%
“…The implicated interactions between the transamination and amino acid metabolism pathways in HCC cells may be involved in the development of HCC mediated by downregulated OTC. Additionally, studies have reported that OTC may influence liver regeneration though participating in certain unidentified signaling pathways, independent of its known enzyme activity (29). Further investigations are required to explain whether the effect of OTC on HCC cells relies on the protein itself or its catalytic properties and possible targets.…”
Section: Discussionmentioning
confidence: 99%